Media Sentiment, Government Supervision Strategy, and Stock Price Fluctuation Risk - Zhu Jufang (Discrete Dynamics in Nature and Society)
From the cross perspective of communication science and administration management, based on complex network theory, this paper constructs a model of stock price fluctuation risk contagion, which comprehensively considers media sentiment and government supervision strategy, and deeply analyzes the contagion mechanism of stock price fluctuation risk under the interaction of media sentiment and government supervision strategy. The main conclusions are as follows: The stock association network established by random way is more likely to cause contagion of stock price fluctuation risk. Media sentiment tendency, media sentiment intensity, and media attention persistence have positive “U” relationship, inverted “U” relationship, and positive correlation with contagion intensity of stock price fluctuation risk, respectively. There is a negative correlation between the strength, persistence, and timeliness of government supervision and the contagion intensity of stock price fluctuation risk. There is a positive correlation between market noise and contagion intensity of stock price fluctuation risk, and market noise has a restraining effect on media sentiment and government supervision strategy. In addition, the stock price fluctuation risk is inherent risk in the stock market, which cannot be eliminated by adjusting media sentiment and government supervision strategy, but its contagion intensity can be effectively controlled.